1986
DOI: 10.1099/00221287-132-9-2611
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Dihydroxyacetone Kinase from Schizosaccharomyces pombe

Abstract: 1Dihydroxyacetone kinase (ATP : dihydroxyacetone phosphotransferase) from Schizosaccharomycespombe has been purified and characterized. It has an M, of 16OOOO and consists of four polypeptides of M, 45000. It shows high substrate specificity, dihydroxyacetone being its only phosphoryl group acceptor and ATP its only phosphoryl group donor; the apparent K, value for dihydroxyacetone was 16 p~ and that for ATP 550 p~. It has a pH optimum of 6.5, requires Mg2+ or Cat+ (the slightly more active ion), and is inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This was clearly substantiated for the DAK1-encoded protein, since a gene deletion abolished measurable DAK activity, whereas DAK1 overexpression led to radically higher levels of DAK activity during growth in glucose medium. In addition, the kinetic properties of the Dak1 protein in S. cerevisiae, with a here reported K m for DHA of 22 M and for ATP of 0.49 mM, are similar to most of the earlier charac- (26,28,34). These values for the yeast enzymes are also in good agreement with K m(DHA) of DAKs from diverse bacterial species (27).…”
Section: Discussionsupporting
confidence: 87%
“…This was clearly substantiated for the DAK1-encoded protein, since a gene deletion abolished measurable DAK activity, whereas DAK1 overexpression led to radically higher levels of DAK activity during growth in glucose medium. In addition, the kinetic properties of the Dak1 protein in S. cerevisiae, with a here reported K m for DHA of 22 M and for ATP of 0.49 mM, are similar to most of the earlier charac- (26,28,34). These values for the yeast enzymes are also in good agreement with K m(DHA) of DAKs from diverse bacterial species (27).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, Schizosaccharomyces pombe and a number of glycerol-utilizing yeasts were assumed to produce DHA phosphate via DHA on the basis of the observation of the absence of glycerol kinase and the presence of glycerol dehydrogenase and DHA kinase (DHAK) (11). Marshall et al (10) purified a DHAK from S. pombe 972h Ϫ which is a key enzyme in the main pathway of glycerol dissimilation and showed that its native form was a molecule composed of four identical subunits with a molecular mass of 45,000 Da. We have found that S. pombe IFO 0354 produces two immunologically distinct DHAKs, and we have characterized these enzymes.…”
mentioning
confidence: 99%